Anti-Reproductive Effects Of Total Glycosides Of Tripterygium Wilfordii In Male House Rat, Rattus Rattus (Applied Biological Research, 2015)
Present study was conducted to evaluate anti-reproductive effects of  total glycosides of Tripterygium wilfordii (GTW) (Thunder God Vine), in  male House rat, Rattus rattus, a predominant rodent pest species found  in commensal situations in Punjab, India. Mature male rats were fed on  bait (cracked wheat and powdered sugar, 98:2) containing 0.1, 0.2 and  0.3% GTW for 10 days in no-choice feeding tests. Results revealed 67.2- 85.2% acceptability of treated bait over untreated bait. Autopsy of rats  after 30 days of treatment withdrawal revealed significant (P≤0.05)  reduction in weights of testes and epididymides. The sperm motility, live  sperm count and sperm concentration in the cauda epididymal fluid of treated rats was also reduced significantly compared to that in untreated  rats. The major abnormality in sperm morphology was sperm head tail  separation. Results suggest the use of GTW for reducing reproduction of  rattus in integration with chemical control.
Keywords: Anti-reproductive effects; glycosides; Rattus rattus; Tripterygium wilfordii